1990
DOI: 10.1530/acta.0.1220145
|View full text |Cite
|
Sign up to set email alerts
|

A polyclonal antiserum against chromogranin A and B - a new sensitive marker for neuroendocrine tumours

Abstract: Chromogranins A, B, and C, proteins that are co-stored and co-released with peptides and amines, have been identified in a variety of neuroendocrine tissues, both normal and neoplastic. We examined the secretion of chromogranin A and chromogranin A + B by hormone-producing tumours in patients with endocrine pancreatic tumours, carcinoid tumours, pheochromocytomas, and small cell lung cancer. The radioimmunoassay determining the plasma concentrations of chromogranin A + B showed a greater sensitivity than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 21 publications
5
39
1
Order By: Relevance
“…However, we confirm that plasma CgA is an excellent predictor of disease, especially in gastroenteropancreatic tumours Eriksson et al, 1990;Nobels et al, 1997;Baudin et al, 1998) which were identified in all cases. As already reported for phaeochromocytomas, in this group a frequent cosecretion of CgA and of other tumoral markers was likewise observed (Nobels et al, 1997;Baudin et al, 1998) and CgA was sometimes found to be the only humoral predictor of disease (Baudin et al, 1998;Ferrari et al, 1998;Nobels et al, 1998).…”
Section: Discussionsupporting
confidence: 76%
“…However, we confirm that plasma CgA is an excellent predictor of disease, especially in gastroenteropancreatic tumours Eriksson et al, 1990;Nobels et al, 1997;Baudin et al, 1998) which were identified in all cases. As already reported for phaeochromocytomas, in this group a frequent cosecretion of CgA and of other tumoral markers was likewise observed (Nobels et al, 1997;Baudin et al, 1998) and CgA was sometimes found to be the only humoral predictor of disease (Baudin et al, 1998;Ferrari et al, 1998;Nobels et al, 1998).…”
Section: Discussionsupporting
confidence: 76%
“…Levels of total circulating hCgA are significantly elevated in phaeochromocytomas, carcinoid and pancreatic endocrine tumours (O'Connor and Deftos, 1986). These data have been confirmed and extended to other neoplasia: neuroblastoma and gastrointestinal tumours (Eriksson et al, 1990;Hsiao et al, 1990;Stridsberg et al, 1995). Other authors have also described how the occurrence of plasma hCgA in prostatic carcinoma may be the sign of an unfavourable evolution (Cussenot et al, 1996;Deftos et al, 1996).…”
mentioning
confidence: 72%
“…Since then, other assays for measurements of hCgA (Dillen et al 1989, O'Connor et al 1989, Eriksson et al 1990, Bender et al 1992, Stridsberg et al 1993, Syversen et al 1994, Corti et al 1996 and bCgA have been reported (Dillen et al 1989, Kawakubo et al 1989. Regionspecific assays for the determination of CgA and CgB have also been published (Tateishi et al 1989, Iguchi et al 1990, McGrath-Linden et al 1991, Kirchmair et al 1994, Syversen et al 1994, Stridsberg et al 1995.…”
Section: Discussionmentioning
confidence: 99%